Learning Curve in Anatomo-Electrophysiological Correlations in Subthalamic Nucleus Stimulation - Hrabovsky, Dušan; Balaz, Marek; Bockova, Martina; Feitova, Věra; Novak, Zdeněk; Chrastina, Jan (Turkish neurosurgery, 2018)
AIM: Advances in neuroradiological planning techniques in deep brain stimulation have put the need for intraoperative electrophysiological monitoring into doubt. Moreover intraoperative monitoring prolongs surgical time and there is potential association between the use of microelectrodes and increased incidence of hemorrhagic complications. The aim of this study was to analyze the correlation between the anatomically planned trajectory and the final subthalamic electrode placement after electrophysiological monitoring in patients with Parkinson"s disease and its change with the increasing experience of the surgical team. MATERIAL AND METHODS: The trajectories of right (first implanted) and left electrodes were compared in the first 50 patients operated on (Group 1) and the next 50 patients (Group 2). RESULTS: In Group 1, 52% of central trajectories were on the right and 38% on the left; in Group 2, the percentage of central trajectories was 76% on the right and 78% on the left; the difference was statistically significant (p=0.021 and 0.001). The difference in the percentage of posterior trajectories reflecting brain shift between the right and left sides was statistically insignificant in Groups 1 (26% and 28%, p=0.999) and 2 (18% and 12%, p=0.549). The percentage of bilateral central electrodes was 14% and 62% in Groups 1 and 2, respectively. CONCLUSION: The correlation between anatomically planned trajectory and final electrode placement markedly improves with the number of patients. However the significant percentage of patients with final electrode trajectory differing from anatomically planned target supports the use of intraoperative monitoring.
Keywords: implantované elektrody; Learning Curve; Humans; mikroelektrody; Clinical Competence; intraoperační neurofyziologická monitorace; lidé středního věku; Deep Brain Stimulation; Intraoperative Neurophysiological Monitoring; Female; Aged; senioři; lidé; nucleus subthalamicus; klinické kompetence; křivka učení; Microelectrodes; Electrodes, Implanted; ženské pohlaví; Male; Middle Aged; hluboká mozková stimulace; Subthalamic Nucleus; mužské pohlaví; Parkinson Disease; Parkinsonova nemoc